2020
DOI: 10.1097/pcc.0000000000002235
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Automated Pediatric Logistic Organ Dysfunction-2 Versus Manual Pediatric Logistic Organ Dysfunction-2 Score for Critically Ill Children*

Abstract: Objectives: The Pediatric Logistic Organ Dysfunction-2 is a validated score that quantifies organ dysfunction severity and requires complex data collection that is time-consuming and subject to errors. We hypothesized that a computer algorithm that automatically collects and calculates the Pediatric Logistic Organ Dysfunction-2 (aPELOD-2) score would be valid, fast and at least as accurate as a manual approach (mPELOD-2). Design: Retrospective cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
0
14
1
1
Order By: Relevance
“…There are also many other classification methods and variations of these machine learning models that could be investigated. Of note, PELOD-2 has a lower AUC in our population than in previously studied populations ( 1 , 10 , 11 ). Although we suspect that this difference is attributable to differences in patient populations, and performance of the PELOD-2 logistic regression model improved after retraining using local data, we cannot exclude other systematic biases in the current work.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…There are also many other classification methods and variations of these machine learning models that could be investigated. Of note, PELOD-2 has a lower AUC in our population than in previously studied populations ( 1 , 10 , 11 ). Although we suspect that this difference is attributable to differences in patient populations, and performance of the PELOD-2 logistic regression model improved after retraining using local data, we cannot exclude other systematic biases in the current work.…”
Section: Discussioncontrasting
confidence: 75%
“…PELOD RF , a random forest-based classifier for predicting mortality using the same variables as the PELOD-2 score, had better discrimination and calibration than PELOD-2 for predicting PICU mortality. Although mortality scores are not typically used at the bedside due to complexity of data collection and chance of human error ( 10 ), they are essential for quality assessment and to control for severity of illness in clinical studies ( 1 , 5 , 6 , 10 ). We found that most machine learning models had better performance than the logistic regression-based PELOD-2 model, even after relearning PELOD-2 model on local data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations